DEVELOPMENT OF VOLLEYBALL SPORT AND ITS IMPORTANCE FOR ATHLETES - Rahmonov Shuhrat Yusupovich (American Journals, 2023)
Volleyball (English: volley volley - "hit" and ball - "ball") is a ball sport played by two teams of 6 players on a court with a net in the middle. It is played on a 9x18 m court divided in the middle by a net (2.43 m high for men's competition and 2.24 m high for women's competition). A volleyball net has 1,000 cells (100 wide and 10 high), and each cell has four sides of 10 cm. One team consists of 6 people and 2 teams play. Players try to hit the ball with their hands and land it in the opponent's field. The ball must be moved to the opponent's side in three hits.
Keywords: players, opponent, developed, field, rules, lider,play part, number, federation